PECULIARITIES OF MOURNER’S SPEECH IN ENGLISH AND UZBEK LANGUAGES AT THE CONDOLENCE CEREMONY - Narmurodova Gulnoza Ilxom Kizi (Journal Park Publishing, 2024)
On the basis of this topic under analysis, the expression of a mourner’s speech in the process of condolence in English and Uzbek languages is highlighted. Ideas about how people express their feelings in sad moments have been proven. The similarities and differences between the English and Uzbek linguoculture in the speech of mourners have been analyzed in both languages.
Keywords: condolence, mourner’s speech, religion, sympathy, linguoculture, contextual analysis, comparative, cross-cultural analysis.